The value relevance of earnings in the return–earnings relation in the Nigerian Deposit Money Banks - Siyanbola Akeem Adetunji (Cogent Business & Management, 2016)
This study was conceived to investigate the extent of relationship between accounting numbers and market values of listed Deposit Money Banks (DMBs) in Nigeria using the Easton and Harris model. Accounting information data were collected from the published financial statements of the sampled DMBs and the market value data were gathered through official daily list of the Nigerian Stock Exchange over a period of nine years (2004–2012). Multivariate regression was used to test the hypothesis of the study. The study established that accounting information of DMBs in Nigeria is value relevant. Though the result established value relevance of accounting information, however, earnings which is reputed to be the most value-relevant account information for financial services firms was found to be irrelevant as its coefficients and p-value were small and insignificant. The study recommends that the management of DMBs in Nigeria should improve on their earnings as doing so will prevent recurrence of stock market crisis of 2008 and 2009.
Keywords: 650